The relations of Sharia Financial Literacy, Financial Inclusion, and Business Sustainability : English - Amiliya, Lya; Syarif, Moch. Edman; Sumiyati; Nugraha, Muhamad Arif; Muhammad Firdaus, Rifqi (Indonesian Journal of Economics and Management, 2025)
This study examines the impact of Islamic financial literacy and Islamic financial inclusion on the business sustainability of MSMEs in the Bandung Raya area. Using a quantitative approach, data were collected from 300 SMEs through structured questionnaires. The findings reveal that Islamic financial literacy significantly enhances business sustainability by fostering informed financial decision-making, ethical management, and resilience. Islamic financial inclusion also plays a critical role, providing MSMEs with access to Sharia-compliant financial services such as financing and investment, which drive growth and competitiveness. Furthermore, the study highlights the mediating role of financial inclusion, amplifying the effects of financial literacy on business sustainability. These results emphasize the interconnectedness of financial literacy and inclusion as key drivers of MSME resilience and sustainability. Stakeholders are encouraged to prioritize financial education initiatives, regulatory reforms, and innovative financial solutions to empower MSMEs and support broader economic development aligned with Islamic principles.